Functional analysis - Lax, Peter D (New Delhi Wiley, 2012)
It is meant as a text, with short chapters in accordance with the author's belief that it is easier to digest this material in small chunks. The first 25 chapters make only modest technical demand on the reader and would serve well as a text for an introductory graduate course on functional analysis. The rest of the book is well suited for a more advanced graduate course on functional analysis in general, or in Hilbert space in particular.
Author index 573-576p.; Subject index 577-580p.; Reprint 2014
Keywords: Hilbert space; Invariant subspaces; Weak convergence; Scattering theory